STUDI EKSPERIMEN TUFT FLOW VISUALIZATION PADA FORWARD WINGTIP FENCE CANT ANGLE 75o TERHADAP KINERJA AERODINAMIKA WING - Melando Sagala; Setyo Hariyadi (Approach : Jurnal Teknologi Penerbangan, 2020)
Winglet is one of the accessories on the aircraft's wing that allows the addition of wing performance without having to widen the wingspan (stretch of the wing). Winglets can be in the form of additional fins that are mounted perpendicular to the wing tips, or can be in the form of extended wings that are bent vertically. The winglet serves to reduce the flow of the vortex at the tip of the wing (tip vortex) caused by the flow of air from the underside of the high-pressure wing to the lower-wing air flow of the lower-pressure wing which results in trailing vortex. The experimental method that will be used in this study is an experimental simulation using a wind tunnel in the Aerodynamic Hangar Lab of Aircraft Engineering Study Program (TPU) at Surabaya Aviation Polytechnic. This specimen is in the form of an Eppler 562 airfoil with a length of 50 cm, and a modified winglet of the Advenced Winglet Forward Fence with a cant angle of 75°, with an angle of attack (angel of attack) 0°, 4°, 10°, 12°, 15°, and 17°. Velocity of freestream is 10 m/s with steady condition. The Re of simulation is = 2,4 x .From the results of the tests that have been carried out, it is found that the aerodynamic performance and the phenomenon of airflow around the airfoil. In the test, there is a difference in the airflow phenomenon behind and on the airfoil body.Keywords: Winglet, Wingspan, Vortex, Tip Vortex, Trailing Vortex